Microbial Biofilms Along a Geochemical Gradient at the Shallow-Water Hydrothermal System of Vulcano Island, Mediterranean Sea - Sciutteri, Valentina; Smedile, Francesco; Vizzini, Salvatrice; Mazzola, Antonio; Vetriani, Costantino (Frontiers in Microbiology, 2022)
Shallow water hydrothermal vents represent highly dynamic environments where strong geochemical gradients can shape microbial communities. Recently, these systems are being widely used for investigating the effects of ocean acidification on biota as vent emissions can release high CO2 concentrations causing local pH reduction. However, other gas species, as well as trace elements and metals, are often released in association with CO2 and can potentially act as confounding factors. In this study, we evaluated the composition, diversity and inferred functional profiles of microbial biofilms in Levante Bay (Vulcano Island, Italy, Mediterranean Sea), a well-studied shallow-water hydrothermal vent system. We analyzed 16S rRNA transcripts from biofilms exposed to different intensity of hydrothermal activity, following a redox and pH gradient across the bay. We found that elevated CO2 concentrations causing low pH can affect the response of bacterial groups and taxa by either increasing or decreasing their relative abundance. H2S proved to be a highly selective factor shaping the composition and affecting the diversity of the community by selecting for sulfide-dependent, chempolithoautotrophic bacteria. The analysis of the 16S rRNA transcripts, along with the inferred functional profile of the communities, revealed a strong influence of H2S in the southern portion of the study area, and temporal succession affected the inferred abundance of genes for key metabolic pathways. Our results revealed that the composition of the microbial assemblages vary at very small spatial scales, mirroring the highly variable geochemical signature of vent emissions and cautioning for the use of these environments as models to investigate the effects of ocean acidification on microbial diversity.